Analysis the Influence of Social Status, Lifestyle, and Prices on Purchasing Decisions Mediated By Payment Digitalization - Rifa'ie, Rizky; Chan, Syafrizal (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze how social status, lifestyle, and price influence purchasing decisions, with a focus on the role of digital payment methods among Andesti Jaya Shop consumers. The research utilized a quantitative approach, surveying 190 respondents from nine locations in Bogor City and Depok City, all of whom had made at least one purchase at Andesti Jaya Shop. Data analysis was conducted using Structure Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that social status and lifestyle do not have a significant direct impact on purchasing decisions. However, both price and the adoption of digital payment methods positively and significantly influence purchasing decisions. Additionally, social status, lifestyle, and price all positively and significantly affect the adoption of digital payment methods. The study also found that digital payment methods fully mediate the relationship between social status and lifestyle on purchasing decisions, and partially mediate the relationship between price and purchasing decisions. These insights suggest that businesses can develop strategies that leverage the positive impacts of pricing and digital payment methods to influence consumer purchasing decisions. For consumers, the study highlights the increasing importance of digital payment methods in shaping purchasing behavior, influenced by social status, lifestyle, and price considerations.